Effect of Radial Shockwave Therapy on Spine Mobility - Kseniya A. Yurku, Victoria A. Zaborova, Mark V. Ivanov, Sergey I. Dzhadayev, Svetlana A. Tkachenko, Shafaei Hassan, Evgenii A. Babydov, Dmitry Yu. Shestakov (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Objective: low back pain has a huge impact on the patient’s quality of life and imposes an economic burden on healthcare systems. New possibilities for low back pain treatment have opened up with the implementation of shockwave therapy. The aim of the study was to evaluate the effect of radial shockwave therapy on the lumbar spine mobility. Methods: a randomized controlled trial was conducted in 75 patients with chronic nonspecific low back pain complaints. Patients were randomized into two groups, depending on their treatment methods. Group I (n=36) received complex treatment with massage and exercise. Group II (n=39) received complex treatment with radial SWT, therapeutic exercise and massage. Flexion and lateroflexion of the lumbar spine were assessed during the study. Results: according to the data obtained, patients in both groups showed a positive trend by the end of the study in all measurements (p<0,05). Pairwise comparison of the results of groups I and II at each stage of the assessment revealed no statistically significant difference (p>0,05). Conclusion: shockwave therapy does not improve spine mobility in patients with chronic nonspecific low back pain.